The Effect of Volume of Goods and Accuracy of Delivery of Goods on Customer Satisfaction Through the Cost Efficiency of Shipping Goods at Shipping Service Companies in Jakarta - Dwi Yulika; Lira Agusinta; Rully Indrawan; Edhie Budi Setiawan (LP2M IAIN Palopo, 2025)
Planning the delivery and distribution of goods from upstream to downstream cannot be separated from several problems related to shipping costs. It is true that, considering the size of the volume of shipping goods, the question arises about how shipping costs depend on this variable. The relationship between the size of the volume of shipping goods and shipping costs is not an easy one. In particular, the influence of costs depending on vehicle capacity constraints is distinguished. On the other hand, the variable of delivery accuracy also greatly influences delivery costs, in the case of some goods that require special handling, this is very much taken into consideration. From these considerations, the author decided to highlight several factors that influence shipping costs, namely the volume, weight of goods and delivery accuracy, which will later influence customer satisfaction, which is carried out through expedition services, forwarders or shipping lines. The results confirm our hypothesis that transportation has the advantage to provide better services for customers in terms of shipping costs by considering aspects of volume and delivery accuracy. Although when evaluating the accuracy of goods delivery, some customers do not pay much attention to this when the production goods they send are general goods, they need to take into account the possible risks that arise when the production goods they send rot quickly or are dangerous goods, because this is important for accuracy of delivery.